2011
DOI: 10.2298/vsp1107550d
|View full text |Cite
|
Sign up to set email alerts
|

The state of oral health in children at the age of 12 in Montenegro

Abstract: Oral health condition in children at the age of 12 in Montenegro does not satisfy. Thus the importance of the modern preventive measures and programmes should be emphasized and applied through the system of primary oral protection and intensively promote oral health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
0
10
0
3
Order By: Relevance
“…In our sample mean DMFT among the VII grade students was 4.36. Epidemiological data from our region showed that mean DMFT value was 3.43 among 12-years old in Montenegro [10], 4.16 in Bosnia and Herzegovina [11], 4.8 in Croatia [12] and 5.8 in Kosovo [13]. Mean DMFT value recorded in the sample from the current study was higher than those recorded among 12-years old in Spain (1.33) [14], Sicily (2.88) [15] or North-European countries with DMFT values below 3 [16].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In our sample mean DMFT among the VII grade students was 4.36. Epidemiological data from our region showed that mean DMFT value was 3.43 among 12-years old in Montenegro [10], 4.16 in Bosnia and Herzegovina [11], 4.8 in Croatia [12] and 5.8 in Kosovo [13]. Mean DMFT value recorded in the sample from the current study was higher than those recorded among 12-years old in Spain (1.33) [14], Sicily (2.88) [15] or North-European countries with DMFT values below 3 [16].…”
Section: Discussionmentioning
confidence: 70%
“…Pr o se čan broj obo le lih stal nih zu ba (KIP) kod uče ni ka sedmog raz re da bio je 4,36. U po re đe nju s epi de mi o lo škim po daci ma iz re gi o na, kod dva na e sto go di šnja ka vred nost KIP je bi la 3,43 u Cr noj Go ri [10], 4,16 u Bo sni i Her ce go vi ni [11], 4,8 u Hr vat skoj [12] i 5,8 na Ko so vu [13]. Vred nost in dek sa KEP zabe le že na u ovom uzor ku da le ko je ve ća od onih za be le že nih me đu dva na e sto go di šnja ci ma u Špa ni ji (1,33) [14], na Si ci liji (2,88) [15] ili u ze mlja ma se ver ne Evro pe, gde je pro seč na vred nost in dek sa KEP ma nja od 3 [16].…”
Section: Diskusijaunclassified
“…Previous research in the area of Bosnia and Herzegovina and neighboring countries [8,9,10] showed high prevalence of caries of permanent teeth in schoolchildren (45-88.35%). Our study showed significantly lower (4.1%) frequency of caries at this age compared to previous studies, which can be explained by the fact that it was period of early mixed dentition and only recently erupting permanent teeth were present.…”
Section: Discussionmentioning
confidence: 89%
“…Dujister et al reported that one of the most important factors that influenced weight gain and growth in children was the impact of oral health on sleeping [27]. It was suggested that since chronic pain negatively affects sleeping, disturbance in production of growth hormones can lead to retardation of growth [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Therefore poor sleeping due to pain may have also affected performance of the athletes in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Oral examinations were conducted using diagnostic dental equipment and performed in accordance with the criteria of the World Health Organization (WHO). For the assessment of caries prevalence, the DMFT index was used [20][21][22]. In order to eliminate inter-examiner variability, all clinical examinations and interviews were carried out at the Kirikkale University (Faculty of Dentistry, Clinics of Operative Dentistry) and were carried out by the same experienced dentist.…”
Section: Methodsmentioning
confidence: 99%